Music in English Language Teaching: Theory into Practice - Coleman, Patrick (CIEX JOURNAL, 2016)
Music has been used in English language teaching for many years with varying degrees of effectiveness. While many teachers see it as an important tool for learning a language and motivating students, there are others who see it as simply a time filler with little value. This last point falls into the category of TENOR (teaching English for no obvious reason, Abbott, 1981). Maybe this is because there has been a disconnection between theory and practice since teachers with little or no pedagogical focus have misused or misunderstood the use of music in their classrooms.